Improving academic writing skill: Difficulties encountered by undergraduates of English studies in Bangladesh - Muniruzzaman, Sheikh Md.; Afrin, Sadia (Englisia Journal, 2024)
Bangladeshi students of English programs encounter some barriers in their attempt to develop academic writing skill at undergraduate level. The majority of the students who study in English programs in Bangladesh receive their primary and secondary schooling in the instruction medium of Bangla, while a few percent in English medium and English version instructions. Testing and assessment in English studies predominantly focuses on academic writing skill and many students cut a sorry figure in formative and summative assessments in the very first semester due to poor writing competence. This study examined two issues: the difficulties that Bangladeshi undergraduates of English studies confront while developing academic writing skill, and the ways to develop L2 English writing skill. Participants of this study were 6 students studying English in different Bangladeshi universities and 3 English teachers who were teaching at tertiary level. Data collection tools were composition writing samples on a selected topic for undergraduates and a semi-structured interview schedule for teachers. Results indicated that poor grammatical competence and brainstorming skill, insufficient vocabulary, inadequate knowledge of mechanics and writing style, and mother tongue interference were the major barriers that Bangladeshi undergraduates of English studies frequently faced while writing in English.